Status, Trends, and Potentials of Turtle Conservation in Bali: A Mini Review - Pelupessy, Yesha Ainesis El Gracianita; Wiradana, Putu Angga; Rosiana, I Wayan; Widhiantara, I Gede (Universitas Airlangga, 2021)
Sea turtles in Bali has been exploited excessively, which caused decrease in population, and this issue has placed sea turtles threatened to extinction. This review article aimed to provide information regarding the status, trends, and potential of sea turtles in Bali. Information given in this article is vital to ensure reliable knowledge not to only understand our current situation, but also to increase efficiency in reliant to the problem sea turtles face. The literature study method is used to write this review paper, namely by accessing a number of research paper published nationally and internationally. It was explained that the status of sea turtles is known to be endangered and law enforcement is not sufficient overcoming the problem. Conservation trends such as nurturing hatchlings have shown to not only help restore the population of sea turtles, but also to bring economic benefits to the conservation sites and the people. Potentials of ecotourism and DNA Barcoding has shown to be effective to benefit the people economically and increase the efficiency of law enforcement and conservation. Solutions and methods of improvement such as ecotourism and DNA Barcoding explained in this article is practical for Bali to adapt, so that sea turtle conservation is capable to overcome its status and incline to its potential.